Web content quality model for massive open online course - Selamat, Ahmad Wiraputra (2021)
Despite its popularity and acceptance since introduced in 2008, the Massive Open Online Course (MOOC) has faced a number of criticisms regarding its content weaknesses such as lack of clarity, unstructured, poor design and ignorance of learner’s diversity. This is due to the lack of understanding among content providers about the quality aspects that contribute to web content. There are number of previous efforts to improve the quality of MOOC, but none were focused on the web content quality from the view of content providers or experts. As a result, most of the internal quality factors were neglected while the operational definition for the MOOC content quality factors is not well-defined. Therefore, this research proposes a web content quality model for MOOC to be referred by the content provider to develop quality MOOC content. In addition, it is as guidance to determine the quality of a MOOC web content. The model which is based on 7C’s Model for Learning Design Framework was initially developed with the determination of quality factors derived from content analysis involving systematic review on literatures, quality factors combination and categorization. The model was then validated by content providers and experts, which involved content validity test, pretesting and survey on acceptability. Data was analyzed using the Rasch Model on its ability to simplify measurement by converting ordinal data to intervals, besides anticipates data fitness statistically. The analysis showed that 52 quality factors along with nine categories were accepted in determining the web content quality for MOOC. In order to measure the model acceptance in a real-world application, the tool which automates the analysis and evaluation of the web content quality for MOOC based on the quality model was developed named MOOC Content Quality Assessment Tool (MOCQAT). MOCQAT was utilized by 42 stakeholders in UPSI as a case study before their acceptance was confirmed through the technology acceptance test. As a contribution, this research produced a comprehensive web content quality model for MOOC along with the definitions and measurement attributes from the perspective of content providers and experts, which is the first to be developed. The acceptability of the model by stakeholders is also proven by the development and technology acceptance test of MOCQAT.